(untitled) (Revista Brasileira de Contabilidade e Gestão, 2019)
We live in a society that has its basis of functioning and survival in mobility, the possibility of movement, the right to come and go, to send and receive. Therefore, the purpose of this article is to analyze the environmental impacts of the four best selling vehicles in 2018. For this, we used the system dynamics methodology through the application of modeling and computer simulation. From the elaboration of a model, scenarios of each vehicle were constructed that were evaluated in a horizon of teen years , verifying, in each situation, the environmental impacts.